2009
DOI: 10.1016/j.seizure.2008.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Modified Atkins diet to children and adolescents with medical intractable epilepsy

Abstract: The aim of the present study was to evaluate the tolerability and efficacy of the modified Atkins diet given to children and adolescents with antiepileptic drug (AED) treatment resistant epilepsy. 15 children with medically intractable epilepsy were enrolled in the study. Inclusion criteria were at least one seizure a week and a trial of at least two AEDs without obtaining seizure freedom documented in a seizure calendar. At baseline subjects initiated a diet with carbohydrates restricted to make up 10 energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 13 publications
6
49
0
1
Order By: Relevance
“…Forty percent responded with a seizure reduction greater than 50% at the 3-month mark of the trial. This study also found that parents were able to comply well with the diet [32].…”
Section: Whole Dietssupporting
confidence: 58%
See 1 more Smart Citation
“…Forty percent responded with a seizure reduction greater than 50% at the 3-month mark of the trial. This study also found that parents were able to comply well with the diet [32].…”
Section: Whole Dietssupporting
confidence: 58%
“…Kossoff and Dorward [31] reported that in several prospective and retrospective studies of children and adults, 45% of patients had a 50% to 90% reduction in seizure frequency, with 28% reporting a greater than 90% seizure reduction. Weber et al [32] enrolled 15 children with refractory epilepsy in a study of the modifi ed Atkins diet, in which parents were instructed to use a formula to calculate the carbohydrate content of the child's food and were given additional instruction on dietary content. Forty percent responded with a seizure reduction greater than 50% at the 3-month mark of the trial.…”
Section: Whole Dietsmentioning
confidence: 99%
“…Dietary therapies have been described in the treatment of epilepsy since 1921 [4]. These include high fat, low carbohydrate diets such as the traditional ketogenic diet [5][6][7], the modified Atkins diet [1,[8][9][10][11][12][13][14], as well as the low-glycemic index treatment [15], and all three have been used primarily in the treatment of children. However, even as long ago as 1930, these treatments have been recognized as beneficial for adults [16].…”
Section: Discussionmentioning
confidence: 99%
“…This was not different than previous reports of the modified Atkins diet alone after 1 month, in which approximately 75% of treated children had moderate to large ketosis. [2][3][4]13 The median fasting serum beta-hydroxybutyrate was 2.4 mmol/L (range: 0.7-38.5 mmol/L).…”
Section: Ketosismentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Although there are advantages compared with the ketogenic diet, the percentage of children with >50% seizure reduction after 6 months in combined prospective trials of the modified Atkins diet is slightly less, 46% versus 56%. [2][3][4]11,13,14 One possible explanation for the lower efficacy could be a less strict initiation period in comparison to the ketogenic diet. Although evidence suggests that initial fasting is not necessary for longterm seizure control, research does demonstrate that higher ketogenic ratios of fat:carbohydrate plus protein (4:1 versus 3:1) are more effective when starting the ketogenic diet and lower carbohydrate limits are more effective (10 versus 20 grams per day) when starting the modified Atkins diet.…”
mentioning
confidence: 99%